Gaining Insights into the Function of Post-Translational Protein Modification Using Genome Engineering and Molecular Cell Biology. Issue 19 (6th September 2019) - Schmidhauser, Meret; Renz, Peter F.; Tsikrika, Panagiota; Freimann, Remo; Wutz, Anton; Wrana, Jeffrey L.; Beyer, Tobias A.
Abstract: Modifications by kinases are a fast and reversible mechanism to diversify the function of the targeted proteins. The OCT4 transcription factor is essential for preimplantation development and pluripotency of embryonic stem cells (ESC), and its activity is tightly regulated by post-transcriptional modifications. Several phosphorylation sites have been identified by systemic approaches and their functions proposed. Here, we combined molecular and cellular biology with CRISPR/Cas9-mediated genome engineering to pinpoint the function of serine 12 of OCT4 in ESCs. Using chemical inhibitors and an antibody specific to OCT4 phosphorylated on S12, we identified cyclin-dependent kinase (CDK) 7 as upstream kinase. Surprisingly, generation of isogenic mESCs that endogenously ablate S12 revealed no effects on pluripotency and self-renewal, potentially due to compensation by other phosphorylation events. Our approach reveals that modification of distinct amino acids by precise genome engineering can help to clarify the functions of post-translational modifications on proteins encoded by essential gene in an endogenous context. Highlights: A blueprint to investigate PTM on proteins encoded by essential genes Phosphorylation of OCT4 on S12 is downstream of CDK7 OCT4 phosphorylated on S12 accumulates in the G2-M phase of the cell cycle in mESCs Ablation of S12 on OCT4 in mESCs by CRISPR/Cas9 results in a mild phenotype Graphical Abstract: Phosphorylation of OCT4 on serine 12. Unlabelled Image